STRATEGI PEMASARAN JAMU HERBAL DI ERA PANDEMI COVID 19 STUDI KASUS UMKM BERKAT MANADO (Herbal Marketing Strategy In The Era Of The Covid Pandemic 19 MSMEs Berkat Manado Case Study) - Febrano A. R. Ngangi; Noortje M. Benu; Audrey J. M. Maweikere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this study is to determine the marketing strategy ofÂ  herbal medicine in the era of the covid 19 pandemic in MSMEs Berkat Manado. The data used in this study are primary data and secondary data. Primary data were obtained from direct interviews with consumers and MSME owners. The number of respondents was 15 consumers who were randomly selected in supermarkets where MSME products were sold. The sampling technique in this study was carried out by accidental sampling or taking respondents as sampling by chance. Based on the results of research on the marketing strategy ofÂ  herbal medicine in SMEs thanks to the pandemic, the implementation carried out by SMEs has been running but there are some that are still not good because they are not optimal due to the limitations of the owner in several aspects such as technology. The strategy carried out by the UMKM is good and very good in the product aspect, namely the quality of raw materials and the large variety of products, in the price aspect, namely the product price range, in the place aspect, namely the ease of buying products, in the process aspect, namely product availability, in the people aspect, namely the seller's initiative towards consumer needs, in the aspect of physical evidence, namely products that are neatly arranged and dust on the packaging. What needs to be improved on the price aspect is giving discounts, on the promotional aspect, namely the variety of promotional media.